Optimum hydrolysis of yellowfin tuna (Thunnus albacares) viscera using a commercial alkaline protease. - Austero, Cassandra Kaye D. (2023.)
Fish processing wastes and by-products are inevitable due to growing food consumption and demand. The application of Response Surface Methodology (RSM) via DesignExpertⓇ is a game-changer in the efficient use of fish processing wastes and by-products, with improved precision of the process conditions, even at scaled-up operations. Thus, this study aimed at optimizing the hydrolysis of yellowfin tuna viscera (YFTV) with the combined effects of the temperature (℃), reaction time (h), and the alkaline protease (EnzaideⓇ) concentration (%) on the solution protein (mg/mL), protein content (%), and the degree of hydrolysis (DH, %). Bradford assay, o-phthaldialdehyde (OPA), and Kjeldahl method were utilized to measure the responses which were used to establish equations. Results showed that at 40℃, in 2.4 h, with 10% enzyme concentration yields highest soluble protein (0.76 mg/mL), degree of hydrolysis (41.31%), and protein content (8.18%) (p<0.05). Optimum conditions were found to yield a desirability value of 0.992. The optimization analysis of the three responses indicates that minimizing the hydrolysis temperature, minimizing the reaction time, and maximizing the enzyme concentration lead to a desirability value that is in close proximity to 1. The findings of this study may be applied in the development of the optimal conditions for the hydrolysis of tuna by-products, resulting in increased protein content and degree of hydrolysis.
Thesis (Undergraduate, Bachelor of Science in Fisheries) Institute of Fish Processing Technology, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, 2023.
Keywords: Fish protein hydrolysates; Tuna, Yellowfin; Fish processing; Thunnus albacares